Antimicrobial resistance pattern of Uro-Pathogens emphasizing non-lactose fermenting gram negative bacilli - Fatima, Ambreen; Rizvi, Mehwish; Sajjad, Mehwish; Gohar, Hareem; Iffat, Wajiha; Bushra, Rabia (Journal of the Pakistan Medical Association, 2024)
Objectives: To identify various species of non-lactose fermenting gram-negative bacilli involved in urinary tract infections, and to determine their antimicrobial resistance pattern. Method: The retrospective, descriptive, cross-sectional study was conducted from January 1 to April 1, 2022, at the Dow University of Health Sciences, Karachi, and comprised data from the institutional diagnostic laboratory that was related to urine samples regardless of age and gender from January 1, 2020, to December 31, 2021. Data was analysed using SPSS version 25. Results: Of the 103,887 urine samples, 41,280(39.7%) were positive, 51,146(49.2%) showed no bacterial growth, 11,000(10.6%) had non-significant bacterial growth and 461(0.4%) had mixed bacterial growth. Of the positive samples, 18359(44.5%) were positive in 2020, and 22,921(55.5%) in 2021. Gram-negative lactose fermenting bacteria included escherichia coli 23,123(22.3%) and klebsiella pneumoniae 2,993(2.9%), gram-negative non-lactose fermenting bacteria included pseudomonas aeruginosa 1,110(1.07%), and gram-positive bacteria included enterococcus 8,008(7.7%). Pseudomonas aeruginosa was most resistant against tobramycin 880(79.3%) and least resistant against piperacillin-tazobactam 146(13%). Conclusion: Piperacillin-tazobactam was highly sensitive drug against non-lactose fermenting uro-pathogens. Key Words: Antimicrobial resistance, Non-lactose fermenting, Gram-negative bacteria, Urinary tract infection.